DNA-based analysis of shark products sold on the Indonesian market towards seafood labelling accuracy program - Asadatun Abdullah; MALA NURILMALA; EFIN MUTTAQIN; IRFAN YULIANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Abdullah A, Nurilmala M, Muttaqin E, Yulianto I. 2020. DNA-based analysis of shark products sold on the Indonesian market towards seafood labelling accuracy program. Biodiversitas 21: 1385-1390. Authentication of fishery products has relied mainly on DNA analysis of mitochondrial genes such as cytochrome c oxidase I (COI) DNA barcoding and cytochrome b (cyt b) gene fragments. The trend of sharks and rays food products trading in Indonesia significantly increased, due to their important role as protein source which may threaten the vulnerability status of some species. This study was aimed to determine the reliability of COI mini- DNA barcode and cyt b fragment for identification of shark species of heavily processed fishery products. We found the mini-DNA barcode was an effective tool to identify the shark species traded in local markets with most of the sample identifies as Carcharhinus falciformis. Our results highlight the urgency of applying DNA-based method as a routine method to control the labelling of Indonesian fish products and to manage sustainable fisheries.